Risk assessment of the causes of cost overrun of project XYZ - Ramadhani, Suci; Ramadyanto, Widodo; Jahroh, Siti (International Journal Labs, 2024)
Cost overrun is a phenomenon that often occurs in the construction of a construction project. The purpose of this study is to analyze the main factors causing cost overrun in project XYZ based on the results of sensitivity analysis to the variables that form RAP. The results show that the cost element of subcontractors has a very large effect on the total RAP of the subcontractor, and the most dominant work affecting is steel work and panel sandwich work. The RAP weight of the work that affects the RAP is between 22.84% and 43.39%, followed by panel sandwich works and bridge steel work. It is recommended that PT X evaluate the performance of each related bureau, especially the estimating and engineering bureaus, in calculating RAP analysis and considering potential long-term risks.